Disadvantaged entrepreneurship and the entrepreneurial ecosystem - Pickernell, David Grant; Battisti, Martina; Dann, Zoe; Ekinsmyth, Carol (Contemporary issues in entrepreneurship research, 2022)
Entrepreneurial ecosystems constructed by disadvantaged entrepreneurs often exist beside, within, and in opposition to 'mainstream' ecosystems focused on high growth high technology entrepreneurial ventures. Disadvantaged Entrepreneurship and the Entrepreneurial Ecosystem addresses the lack of current research concerning disadvantage using an entrepreneurial ecosystem lens, and the failure of entrepreneurship policy to widen engagement in entrepreneurship for disadvantaged people and places. Drawing together issues affecting disadvantaged entrepreneurs as they struggle to access, interact with, and benefit from, the traditional entrepreneurial ecosystem (EE), these findings highlight the importance of their motives for entrepreneurial activity, their resources, and how access to these are affected by issues such as gender and migrant status. The research in this book also suggests policymakers need targeted, supportive, business-support programs taking into consideration the multiple challenges disadvantaged entrepreneurs typically face.